Apartheid Colonialism, Gendered Crime, and the Domestic Gothic in Mary Watson's The Cutting Room. Issue 1 (2nd January 2020) - Burger, Bibi
Abstract : Mary Watson's gothic novel, The Cutting Room (2013), deals with a woman who does not feel at home in her house. Her unease can be attributed to her conflicted feelings about being a wife in South Africa's colonial and apartheid history, as well as to a fear of crime. Using feminist theories of women's relationship to the domestic sphere, Freud's writing on the unheimlich as well as Homi K Bhaba's notion of the "postcolonial unhomely", I argue that the genre of the gothic provides appropriate metaphors and an aptly uncanny atmosphere for the exploration of a South African woman's complex relationship with the home.